Peranan Dewan Perwakilan Rakyat Daerah (DPRD) Dalam Implementasi Kebijakan Pendidikan Dasar Di Kabupaten Pati - KUSMIATI, Nanik (2012)
The purposes of this research is to: (1) describe the characteristics the role of parliament in policy governance of basic education in the District of Pati. (2) Describe the characteristics of the role of parliament in financial policy in the District Primary Education Pati. This is a qualitative research with Ethnography design, because this design is precise to analyze social phenomena. Method of collecting data has been done by interview with informants, including key informant and other ones, observation during activities, and documentation parliament profiles and photos. Data analyzing has been done by analyzes interactive model, consist of data reduction, data display and verification for several times until data completed. Validity for this data is tested by data triangulation (by comparing data from different sources) and methods triangulation (by comparing data from different methods). The result of this research such as are: (1) Characteristics of the role of parliament in the governance of basic education policy in Pati District includes roles in the planning, implementation and supervision. Role of Parliament in the planning include a representative function, budgeting, legislative and oversight functions direferentasikan RPJMD preparation. Role of Parliament in implementing policy governance of basic education is realized through a functioning parliament as a function as a regulator, policy making, and budgeting, represent the demands of the people, advocacy anggregasi, administrative oversight, legislation, budgeting and supervision. (2) Characteristics of the role of parliament in financing policy in Pati District Primary Education covers the role of Parliament in the legislative function, the function of budgeting, and monitoring functions. The role of Parliament relating to the legislative function is implemented in the form of the decision, set budgets, to supervise the implementation of legislation and budget. The role of Parliament relating to the budgeting functionality is implemented in the form of preparing, planning, approve or reject the proposed budget and set a budget. The role of Parliament relating to the implementation of education financing policies implemented from the planning, execution and reporting, and evaluation. The role of Parliament relating to the monitoring function is implemented in accordance with the duties and authority of governance in areas including public services such as education funding policy to be effective and efficient. Advice submitted to Parliament Pati Pati District Education Office, and schools should promote commitment, performance and its role in managing the governance of education policy and financing in the hope of improving the progress of education in the District of Pati.